Characteristics and Behavior of Elderly-onset Inflammatory Bowel Disease: A Multi-center US Study. Issue 9 (September 2016) - Hou, Jason K.; Feagins, Linda A.; Waljee, Akbar K.
Abstract : Background: Existing data conflict regarding differences in inflammatory bowel disease (IBD) characteristics between adult-onset and elderly-onset IBD. IBD extent and behavior are strong predictors of IBD-related surgery and complications. The aim of this study was to compare disease characteristics and behavior of adult- and elderly-onset IBD in a multi-center US study. Methods: We performed a multi-center retrospective cohort study of patients with IBD. Chart review was performed to confirm IBD diagnoses and extract data regarding IBD characteristics, medications, surgery, cancer, and death. Patients were classified based on age at IBD diagnosis as adult onset (18–64 years) or elderly onset (≥65 years). Results: A total of 1665 patients were confirmed to have IBD; 272 patients were ≥65 years at IBD diagnosis. Whites were more likely than non-whites to have elderly-onset IBD (adjusted odds ratio 2.26, 95% confidence interval 1.36–3.76). Patients with ulcerative colitis were more likely than CD patients to have elderly-onset IBD (aOR 1.50, 95% confidence interval 1.11–2.03). Compared with patients with adult-onset CD, patients with elderly-onset CD were more likely to have isolated colonic disease and nonstricturing, nonpenetrating phenotype, but less likely to have perianal complications or receive immunosuppressants. Rates of bowel resection, and both colonic and extra-colonic malignancies did not differ based on age of IBD onset. Conclusions: There are several significant differences in the disease characteristics between adult- and late-onset IBD; these differences may reflect differences in natural history of IBD and influence approaches to management among patients with elderly-onset IBD. Abstract : Article first published online 2 August 2016.